Analisis Faktor Alam dan Manusia Penyebab Bencana Banjir di Daerah Aliran Sungai - Yuri, Cicia Oktri; Chikal, Chikal; Rinal, Rinal; Ikhwan, Ikhwan (Indo-MathEdu Intellectuals Journal, 2025)
Floods are disasters that frequently occur in river basin areas and are influenced by various natural factors as well as human activities. This research aims to comprehensively analyze the causes of flooding in river basins, including high rainfall, topographical conditions, erosion, and ecological damage due to land use changes and development in water catchment areas. Additionally, aspects of drainage management, waste accumulation, and river channel capacity are also examined as human factors that exacerbate flood risk. The research method employs a qualitative approach with the collection of secondary and primary data, namely books and scientific articles, to obtain a comprehensive overview. The analysis results indicate that the interaction between natural and human factors significantly increases the frequency and impact of floods in the watershed. Therefore, integrated mitigation efforts are needed that involve sustainable environmental management and spatial planning to reduce the risk of flooding in the future.